SERVQUAL Digital Challenges in Serving Foreign University Graduates in Indonesia - Hermawan, Hermawan; Sugiyono, Sugiyono (Jurnal Manajemen Pelayanan Publik, 2024)
This study is based on the problems faced regularly by foreign university graduates in ensuring the legality of the diplomas they have obtained, where the process takes a lot of time, is impractical, has high costs, and has been quite troublesome for the graduates, upon returning to their homeland. The problem of this research is how to optimize digital-based services by the Directorate of Learning and Student Affairs of the Republic of Indonesia; so, that foreign students can conform to minimum service standards. This study aims to analyze the implementation of online services for equalizing diplomas for foreign university graduates. Additionally, the method used is descriptive qualitative. The study results show that there are supporting and inhibiting factors for electronic services in higher education, especially at the institutional, organizational, and personnel levels. These issues must be addressed for equal access to services and easy recognition of foreign diplomas. It was concluded that the government as an education service provider needs innovation which can also better guarantee the validity of college graduation, while the process still refers to SERVQUAL standards. This study recommends an innovative model that has operational and strategic value for reforming higher education administrative services.